2022
DOI: 10.1111/ijac.14160
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural, electrical, and mechanical properties of conductive SiC ceramics fabricated by spark plasma sintering

Abstract: Nitrogen (N)-doped conductive silicon carbide (SiC) of various electrical resistivity grades can satisfy diverse requirements in engineering applications. To understand the mechanisms that determine the electrical resistivity of N-doped conductive SiC ceramics during the fast spark plasma sintering (SPS) process, SiC ceramics were synthesized using SPS in an N 2 atmosphere with SiC powder and traditional Al 2 O 3 -Y 2 O 3 additive as raw materials at a sintering temperature of 1850-2000 • C for 1-10 min. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
(181 reference statements)
0
2
0
Order By: Relevance
“…Element dissolution, diffusion, and grain growth are all involved in the solution‐precipitation process, which has an important influence on the electrical conductivity of ceramics containing SiC semiconductor phases 30 . It has been demonstrated that nitrogen elements could dope into SiC crystals during their grain growth in the LPS process 31,32 . After doping, a donor level is created in the band gap of β‐SiC by replacing carbon atoms with incorporated nitrogen atoms, improving the electrical conductivity of ceramic composites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Element dissolution, diffusion, and grain growth are all involved in the solution‐precipitation process, which has an important influence on the electrical conductivity of ceramics containing SiC semiconductor phases 30 . It has been demonstrated that nitrogen elements could dope into SiC crystals during their grain growth in the LPS process 31,32 . After doping, a donor level is created in the band gap of β‐SiC by replacing carbon atoms with incorporated nitrogen atoms, improving the electrical conductivity of ceramic composites.…”
Section: Resultsmentioning
confidence: 99%
“…30 It has been demonstrated that nitrogen elements could dope into SiC crystals during their grain growth in the LPS process. 31,32 After doping, a donor level is created in the band gap of β-SiC by replacing carbon atoms with incorporated nitrogen atoms, improving the electrical conductivity of ceramic composites. During sintering of the Si 3 N 4 -SiC ceramic nanocomposites, the nitrogen elements from the nitrogen atmosphere and Si 3 N 4 particles dissolve into the intergranular phases and then incorporate into SiC nanograins during grain growth.…”
Section: Electrical Conductivitymentioning
confidence: 99%